Insegnanti inclusivi: un'indagine empirica sulla formazione specialistica degli insegnanti di sostegno - Anna Maria Ciraci; Maria Vittoria Isidori (LED Edizioni Universitarie, 2017)
The essay concerns the outcomes of an empirical-experimental research conducted in the annual teacher specialization for special educational needs, at the University of L'Aquila in the academic year 2014/15. The survey is included in the research on the effectiveness of the training courses for teachers. It involved 115 teachers and aimed to investigate whether there has been an actual increase in specific professional skills, school enrollment, among those who followed the specialization course. The data was obtained from the comparison between the control group, consisting of teachers who haven't begun yet the formation, and the experimental group, constituted by the same teachers at the end of the specialization course. Even if data shows, at different levels of significance, a positive general effect of the course, they do not show appreciable differences in some important didactic-evaluative and communicative-relational dimensions, fundamental to the inclusion process, such as the individualization of didactic intervention, the sharing of training objectives and teaching and evaluation methods with class teachers, the collaboration with families and with operators of social and health services. Teachers, also, claim to have gained more confidence in their professionalism and more security in dealing with the problems encountered in the class. However not all the teachers feel able to apply the educational and didactic strategies learned and to offer their support «to the class». Finally, it appears necessary to review some aspects related to the content of the course and the didactic-training methods used.